2019
DOI: 10.5194/tc-2019-80
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Micromechanical modeling of snow failure

Abstract: Abstract. Dry-snow slab avalanches start with the formation of a local failure in a highly porous weak layer underlying a cohesive snow slab. If followed by rapid crack propagation within the weak layer and finally a tensile fracture through the slab appears, a slab avalanche releases. While the basic concepts of avalanche release are relatively well understood, performing fracture experiments in the lab or in the field can be difficult due to the fragile nature of weak snow layers. Numerical simulations are a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The PST system was generated using commercial DEM software; PFC3D (v5) (). For a detailed description of the DEM model for snow, and in particular how particle (and particle contact) parameters relate to macroscopic snow parameters, refer to Bobillier and others (2020). Recently, Bobillier and others (2021) modelled the PST design and showed that crack propagation in weak snow layers can be reproduced with their DEM model (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PST system was generated using commercial DEM software; PFC3D (v5) (). For a detailed description of the DEM model for snow, and in particular how particle (and particle contact) parameters relate to macroscopic snow parameters, refer to Bobillier and others (2020). Recently, Bobillier and others (2021) modelled the PST design and showed that crack propagation in weak snow layers can be reproduced with their DEM model (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Bobillier and others (2020) presented a 3-D DEM model to reproduce failure in a layered snow sample. DEM, first introduced by Cundall and Strack (1979), is composed of a large number of discrete connected and interacting particles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned, the advantage of this approach is that parameters of the Sticky Hard Spheres model (volume fraction and coordination number) can be directly evaluated based on X-ray tomographic images by matching correlation functions 31 . While several recent numerical studies have analyzed the mechanical response of porous brittle solids like snow based on the real samples’ microstructures 18 , 19 , 21 , it has been recently shown that simplified structures made of spherical particles can be used to reproduce accurately important features of snow mechanics in the brittle range for different processes: failure initiation 35 , 36 , crack propagation 9 , 10 , snowflake fragmentation 37 , wind blowing snow 38 , snow granulation 39 and avalanche impact pressures 40 . One the one hand, this simplification makes us loose important information about the microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…Such an avalanche releases due to the failure of a weak layer buried below a cohesive snow slab (Schweizer et al, 2016). Although a lot of progress has been done regarding the understanding of slab avalanche release processes, including the onset and dynamics of crack propagation (Gaume et al, 2013;Bobillier et al, 2021;Trottet et al, 2022), the evaluation of the size of avalanche release zones still remains a major issue. This difficulty impedes avalanche forecasting and hazard mapping procedures which rely on the avalanche release size as input.…”
Section: Introductionmentioning
confidence: 99%